Assessing the state-of-knowledge of bees and their pollination services in Colombia - Morales-Rozo, Clara; Morales-Rozo, Andrea; Restrepo Calle, Sebastián; López-Uribe, Margarita M.; Gonzalez, Victor H. (Journal of Melittology, 2025)
Understanding the state of knowledge of pollinators and their interactions with plants is critical for planning and developing effective conservation strategies. Despite the many challenges in studying bee diversity and pollination services in Colombia, this contribution represents a preliminary effort to quantitatively assess existing information gaps. This is particularly important in regions of high biodiversity that have historically been understudied and are now facing significant environmental pressures from human activities. Based on a review of the literature, we present the first quantitative assessment of bee biodiversity, bee-plant interactions, and pollination services in Colombia. We analyzed 88 publications and extracted data across the following categories: i) bee diversity, ii) bee-plant interactions, and iii) assessment of pollination services. For each bee and plant species documented, we recorded taxonomic and geographic information, resulting in a total of 8,099 records. Most records report information on bee diversity (58%), followed by bee-plant interactions (29%), and assessments of pollination services (13%). Most records correspond to corbiculate bees (Apidae) from modified ecosystems in the Andean region, particularly at lower elevations. Studies evaluating pollination services are limited and tend to rely on qualitative methods. The implications of these results, taxonomically and geographically skewed towards common taxa and Colombia’s most populated areas, are discussed in the context of ongoing efforts to conserve pollinator populations in the country.